Microstructural and Mechanical Properties of Underwater Wet Welded SS400 Steel / N. M. L. P. K. Yasari ...[et al.] - K. Yasari, N. M. L. P.; Muhayat, Nurul; Triyono, Triyono; Saputro, Y. C. N. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Underwater wet welding is mainly used for repairing and maintenance of marine constructions. Shielded Metal Arc Welding (SMAW) is widely used in underwater wet welding. To investigate influence of welding parameters on weld joint of underwater wet shielded metal arc welding (SMAW), weld currents and electrode types were varied during welding process in the trial pool with water depth of 2.5 m. The non-destructive and destructive test including X-ray analysis, microstructure investigation, tensile, impact and hardness test were performed. The results reveal that there were a lot of defects for all specimens in the underwater wet welded joint due to the interfering environment. Due to these defects, the tensile strength was almost the same, it only increased slightly when the welding electric current increased. The increasing penetration due to increasing weld current was the main reason for this case. The highest hardness was found at Heat Affected Zone (HAZ) close to the fusion zone.